Vasculitic Ulcers. (March 2016) - Papi, Massimo; Papi, Claudia
Vasculitic ulcers are an emerging problem in wound care that needs to be well defined and adequately approached by caregivers. Cutaneous vasculitis includes several inflammatory disorders that compromise microvessels and specifically the cutaneous vascular system: arterioles, capillaries, postcapillary venules. The pathogenetic role of circulating immunocomplexes and autoantibodies (antineutrophil antibodies) in these diseases has been widely demonstrated in animal models and in humans. Vasculitis can be limited to the skin or represent the cutaneous signs in case of systemic vasculitis with visceral involvement. The injury of cutaneous microvessels may result in impairment of blood flow and consequent focal ischemia and formation of skin ulcers. The ulcers are often multiple and localized on the lower leg and foot where the microcirculatory anatomy and rheologic dynamics are predisposing factors. Approximately 3% to 5% of skin ulcers may be caused by a vasculitic disorder.